2008
DOI: 10.1007/s11104-008-9587-3
|View full text |Cite
|
Sign up to set email alerts
|

Surface soil carbon size–density fractions altered by loblolly pine families and forest management intensity for a Spodosol in the southeastern US

Abstract: The effects of genotypic differences on soil organic carbon (SOC) cycling and their interactions with forest management systems are poorly understood. This study was undertaken to examine the effects of family and family × management interactions on SOC and to evaluate the distribution of SOC across different size-density fractions in a forested Spodosol. The study site consisted of a 6-year-old loblolly pine plantation that was managed under two intensities (high and low level of fertilization and chemical un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…In addition, losses of labile fraction organic C after forest transition mainly occurred in 0-10 cm topsoil. Our results are consistent with the previous findings (Guo and Gifford 2002;Chen et al 2004a;Sarkhot et al 2008).…”
Section: Effects Of Forest Conversion On Soil Labile C Fractionssupporting
confidence: 94%
“…In addition, losses of labile fraction organic C after forest transition mainly occurred in 0-10 cm topsoil. Our results are consistent with the previous findings (Guo and Gifford 2002;Chen et al 2004a;Sarkhot et al 2008).…”
Section: Effects Of Forest Conversion On Soil Labile C Fractionssupporting
confidence: 94%
“…Some studies also found that the LFOC was higher at the soil surface, which was strongly related to root carbon inputs [45] and other organic residues accumulated in this layer. Our results are consistent with the previous findings [12, 46]. In this study, the higher LFOC at the 0–15 cm layer in the thinned and underplanted stands could be related to more root and litterfall carbon inputs (Table 2).…”
Section: Discussionsupporting
confidence: 94%
“…To the best of our knowledge, this study is the first to specifically address the effect of forest types on SOC stabilization through soil aggregation and soil physical fractions in a natural ecosystem. The very few studies focusing on this topic took place in managed plantation systems (e.g., Blanco-Canqui et al, 2007;Gama-Rodrigues et al, 2010;Quideau et al, 1998;Saha et al, 2010;Sarkhot et al, 2008), where soil disturbance is high and naturally-associated understory is generally lacking. In addition, the tree species selected in these studies were mostly genetically improved species [e.g., loblolly pine {Pinus taeda L.) and hybrid poplar clones].…”
Section: Discussionmentioning
confidence: 99%